How do you multiply e^((23 pi )/ 2 ) * e^( pi/2 i ) e23π2eπ2i in trigonometric form?

1 Answer
Jul 17, 2018

color(crimson)(e^((23 pi)/(2) i) * e^(( pi)/2 i) = -1e23π2ieπ2i=1

Explanation:

e^((23 pi)/(2) i) * e^(( pi)/2 i)e23π2ieπ2i

e^(i theta) = cos theta +i sin thetaeiθ=cosθ+isinθ

:. e^((23 pi)/(2) i) = (cos (23 pi)/(2)+ i (sin 23 pi)/(1))

= 0 - i , IV Quadrant

:. e^(( pi)/2 i) = (cos ((pi)/2)+ i sin ((pi)/2))

= 0 + i, I Quadrant

:. e^((23 pi)/(2) i) * e^(( pi)/2 i)

=( 0 - i ) - ( 0 + i)

color(crimson)(e^((23 pi)/(2) i) * e^(( pi)/2 i) = -1